Economic Burden of Diabetic Foot Ulcers Across Nations: A Scoping Review - Nur Alaydrus; Chriswardani Suryawati; Puji Harto (Indonesian Journal of Global Health Research, 2025)
Diabetic foot ulcers (DFUs) are among the most severe complications of diabetes mellitus, leading to significant morbidity, hospitalizations, and healthcare costs. The economic burden of DFU treatment is primarily driven by hospitalization expenses, surgical interventions, and complications such as nephropathy, retinopathy, gangrene, and osteomyelitis. Objective: This study examines the direct medical costs associated with DFU inpatient care, identifying key cost drivers and variations across different healthcare systems. Method: A scoping review was conducted using PubMed, PubMed Central, and ScienceDirect to analyze peer-reviewed studies published between 2014 and 2024. The review focused on DFU-related hospitalization costs, surgical expenditures, and the impact of comorbidities on financial burden. Results: Hospitalization constituted the largest cost component, with expenses escalating due to surgical procedures, particularly amputations. Economic disparities between high-, middle-, and low-income countries influenced DFU-related expenditures, highlighting differences in treatment accessibility and cost structures. Conclusions: Standardized management strategies and cost-effective interventions are essential to optimize resource allocation and improve patient outcomes. This study provides insights into the financial challenges of DFU treatment, emphasizing the need for healthcare policy reforms to mitigate economic burden and enhance care efficiency.